Occurrence, antimicrobial susceptibility, and resistance genes of Staphylococcus aureus in milk and milk products in the Arsi highlands of Ethiopia - Deddefo, A.; Mamo, G.; Asfaw, M.; Edao, A.; Hiko, A.; Fufa, D.; Jafer, M.; Sombo, M.; Amenu, Kebede (Springer, 2024)
Background